Granular cell tumor in a child: A rare case report - Zeynep Sagnak Yilmaz; Safak Ersoz (Wolters Kluwer Medknow Publications, 2020)
A granular cell tumor (GCT) is a rare, usually benign soft tissue neoplasm that is commonly seen in the head and neck region. It is derived from the Schwann cells of the peripheral nerves. GCT is uncommon in children. 6-year-old girl was referred to our hospital for swelling over her left scapula, and a surgical excision was performed to remove the mass. Microscopically, the tumor was composed of cells with large granular cytoplasm and small oval to round nuclei. These cells stained positively for the following proteins: S-100, CD68, neuron-specific enolase, calretinin, and inhibin A. A GCT is usually benign, with a good prognosis, and less than 2% of the cases are reported to be malignant. It is worth noting that such tumors may arise in atypical locations and there is a possibility of malignancy.